Prime Minister Decree No. 2310/2017 Promulgating The Executive Regulations fo The Investment : The executive regulations of the investment law = اللائحة التنفيذية لقانون الاستثمار - Egypt; The middle east library for economic services, translator. (2025)
Prime Minister Decree No. 2310 of the Year 2017; Promulgating the Executive Regulations of the Investment Law Promulgated by Law No. 72 of the Year 2017 Part-1: General provisions Chapter - 1: The activities and fields subject to the provisions of the investment law Chapter - 2: Community responsibility of the investor Part - 2: Investor-Related Facilitation and Incentives Chapter - 1: Regulation of the residence of non-Egyptians investors and the employment of foreign workers Guarantees Chapter- 2: Chapter - 3: Special and additional incentives 22 24 Part - 3: Investor service center Chapter - I: Organization of the investor service center and investment manuals and procedures Accreditation offices and certificates Chapter – 3: Incorporation of companies - automation - liquidation 3= Prior approval and one approval Allocation of real estates required for investment 28 Chapter - 2: Chapter - 4: Chapter - 5: Part- 4: The investment, technological and free zones Chapter - 1: Chapter- 2: Technological zones Chapter - 3: Investment zones Free zones Part - 5: Organization of the investment environment Chapter - 1: Chapter - 2: Entities in charge of the investment affairs Subsequent control, inspection and governance procedures Grievances Chapter-3